SKILL DEVELOPMENT TRAINING FOR MSME ACTORS IN BANDAR AND BANDAR MASILAM DISTRICT, SIMALUNGUN REGENCY - Sofiyan; Lora Ekana Nainggolan; Nana Triapnita Nainggolan; Darwin Lie; Robert Tua Siregar (RADJA PUBLIKA, 2025)
Skills and digital training for MSME actors is a strategic effort to improve competence in the use of digital technology to strengthen and develop businesses. The activity, which lasted for three days, from Monday, Dec 15, 2025 to Wednesday, Dec 17, 2025, aimed to equip participants with practical skills in the fields of digital marketing, financial management, and operational efficiency. The material includes the use of social media, digital systems, and marketing techniques according to market trends, so that it is expected to be able to increase the competitiveness, effectiveness, and sustainability of MSMEs in the midst of the challenges of globalization and digital transformation.